2012
DOI: 10.3892/or.2012.1713
|View full text |Cite
|
Sign up to set email alerts
|

Real-time bioluminescence and tomographic imaging of gastric cancer in a novel orthotopic mouse model

Abstract: Abstract. Gastric cancer is the second leading cause of cancer mortality worldwide. Understanding the multistep process of carcinogenesis of gastric cancer is pivotal to develop novel therapeutic strategies. Molecular imaging in preclinical cancer models bridges the gap of laboratory-based experiment and clinical translation. To this end, the human gastric cancer cell line SGC-7901 was established to stably express luciferase and GFP by lentiviral transduction (SGC7901-Luc-GFP). Preclinical models were develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Our study shows that mouse weight did not differ between tumour bearing and non-bearing mice even once tumours and metastasis were well established. During the experimental duration, mice appeared healthy and active with no evidence of cachexia and lethargy which was observed in other studies 25 . Due to extensive tumour infiltration into the stomach it was not possible to determine tumour weight even at the time of autopsy.…”
Section: Discussionsupporting
confidence: 81%
“…Our study shows that mouse weight did not differ between tumour bearing and non-bearing mice even once tumours and metastasis were well established. During the experimental duration, mice appeared healthy and active with no evidence of cachexia and lethargy which was observed in other studies 25 . Due to extensive tumour infiltration into the stomach it was not possible to determine tumour weight even at the time of autopsy.…”
Section: Discussionsupporting
confidence: 81%
“…After xenografts were grown in the mice for five generations, they were transplanted into the subserosa of the greater gastric curvature and observed for metastasis. This is an orthotopic mouse model that mimics gastric cancer metastasis, including lymph node and peritoneal transplantation metastases 37, 49. Using the AEG‐1 stable knockdown cell lines in this model, we revealed that silencing of AEG‐1 expression not only inhibited tumour growth in parallel with decreased expression of eIF4E, MMP‐9 and Twist, but it also inhibited the lymph node and peritoneal metastasis of gastric cancer.…”
Section: Discussionmentioning
confidence: 94%
“…As inoculating SGC7901 cells directly to the subserosal layer of the greater gastric curvature results in almost negative lymph node or peritoneal metastasis, we used a model reported by Hu et al . 37 Briefly, SGC7901‐AEG‐1_shRNA cells with stable AEG‐1 silencing and the control SGC7901‐scramble_shRNA cells were inoculated subcutaneously into the flank region of nude mice to establish a xenograft mouse model. When the diameter of the xenografts reached 5 mm, tumours were isolated and sheared into 1–2 mm 3 pieces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the incision in the abdominal wall and skin was closed with Prolene suture. 21 One week after the SGC7901-Luc-GFP cells were inoculated, 8 mg/kg docetaxel (Taxotere, Sanofi-Aventis) or 0.9% saline was assigned to the gastric cancer-bearing mouse for treatment once a week. After 3 weeks of treatment, filtersterilized D-luciferin solution (150 mg/kg body weight) was injected into the mouse peritoneal cavity 10 min prior to bioluminescent image acquisition.…”
Section: A Gastric Cancer-mimic Simulationsmentioning
confidence: 99%